Development of E-Brochure Media Based on The Collection of The Tridaya Eka Dharma Struggle Museum on The Material of The Struggle to Maintain Independence for Class XII Students of SMAN 4 Bukittinggi - Rahmi Adisti; Ahmal Ahmal; Refly Surya Barkara (Global READ Center, 2026)
This study aims to develop an E-Brochure learning media based on the Tridaya Eka Dharma Struggle Museum collection to improve students' understanding in learning history. This research was conducted at SMAN 4 Bukittinggi, focusing on history lessons for Grade XII students. The background of this research arose from the lack of student interest in history lessons due to conventional teaching methods. To address this problem, this study developed an E-Brochure learning media that allows students to learn about museum collections online. This study followed the Research and Development (R&D) method using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. Data collection involved observation, interviews, and questionnaires distributed to students and history teachers. The E-Brochure learning media was validated by media and history material experts before being trialed on small and large groups of students. The findings showed that the E-Brochure learning media was effective in increasing student motivation and engagement in history lessons. Students showed a higher level of enthusiasm and understanding when using the e-brochure compared to traditional learning methods. In conclusion, the e-brochure learning media based on the Tridaya Eka Dharma Struggle Museum collection can be innovative in making history learning more interesting.